The Precarious Lives of Homeless Scavengers in Tokyo Before and After the 2008 Crisis - Wickens, Matt (Lidé města, 2022)
Awareness of poverty in Japan significantly increased after the bubble economy ended in 1991. The presence of older men, approaching or past retirement age, living in blue tents and on park benches, was one of the first to challenge the assumption of a classless Japan. One strategy for men experiencing homelessness to alleviate their hardships and survive is to gather and sell aluminium cans. This paper ethnographically explores their precarious work and documents the various patterns of gathering and selling cans, while also looking at the impact of both local and global forces (neoliberalism) on their work. Based on fieldwork that included the economic recession of 2008–2009, I observed six months of the work of the homeless during economic stability and six months during a severe recession. My research shows how homeless men used the work of gathering and selling cans to survive during a stagnant economy and then adapted to a brutal recession, which resulted in much lower income for their labour as the price of aluminium significantly decreased. I argue that their work was affected by the global economy and that collecting cans and earning money helped homeless men survive through the crisis. Finally, I conclude that earning money via selling cans allowed the men to maintain their self-respect and pride, have a sense of purpose, buy daily necessities, and occasionally splurge on entertainment.